Dekonstruksi Kaidah Imlā’iyyah dalam Komentar Fusha Pada Konten Kasidah di Instagram - Saepudin, Asep Ahmad; Mahliatussikah, Hanik; Murtadho, Nurul; Wicaksono, Meidias Abror; Hleihel, Reem (Aphorisme: Journal of Arabic Language, Literature, and Education, 2026)
This study examines the deconstruction of Arabic orthographic norms in digital communication by analyzing Fusha comments posted in response to Qoshidah content on Instagram. Employing a qualitative netnographic approach adapted from Kozinets. The population comprised Fusha comments on Qoshidah-related Instagram posts, and samples were purposively selected from three highly interactive posts published by @osama_aburmaileh in April–May 2026. Data were collected through passive observation, documentation, screenshot capture, and transcription of comments containing orthographic deviations. Primary data consisted of user-generated comments, supported by relevant literature on Arabic orthography, Computer-Mediated Communication, and digital sociolinguistics. Data were analyzed using systematic error analysis integrated with netnographic interpretation. The findings indicate that orthographic deviations are systematic rather than random. Omissions of hamzah, particularly hamzah qath‘ and hamzah washl, constitute the most frequent category. Other recurrent patterns include word fusion, letter substitution, and expressive letter reduplication. These forms reflect users’ tendency to prioritize communicative efficiency, typing speed, and interpersonal expressiveness over adherence to formal orthographic conventions. The study concludes that digital communication functions as a catalyst for sociolinguistic adaptation, in which traditional Fusha orthography is simplified to accommodate the practical demands of online interaction. Consequently, Arabic language instruction should integrate both conventional Imla rules and contemporary digital writing practices.